MANDATORY VACCINATION AND FUNDAMENTAL RIGHTS - BIOY, Xavier (MEDECINE LEGALE DROIT MEDICAL, 2025)
The meeting between the obligation to be vaccinated and the fundamental rights need a thorough analysis which relates both to the identification of the many rights, objective and subjective, which are concerned and to the nature of the control used by the judges, both abstract and concrete, general and individual. The analysis reveals that this confrontation most often boils down to the abstract proportionality of the interference, almost always justified, of public health order. However, the logic of fundamentality also opens up to a concrete control of the way in which public power takes the place of individuals in the balance between their own subjective rights. This can lead to developing the logic of conscientious objection.